2019
DOI: 10.1037/pag0000386
|View full text |Cite
|
Sign up to set email alerts
|

A trouble shared is a trouble halved: Age differences in emotional experience and expression during couples’ conversations.

Abstract: Although emotional experience and expression are strongly tied to social contexts, most age-comparative studies have used an individualistic approach. The few dyadic laboratory studies that exist have focused on discussions about conflicts and have suggested that older couples experience and express less negative emotion than younger couples. However, recent studies have emphasized the context dependency of age differences in emotional reactivity. More concretely, in situations such as conversations in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 79 publications
2
7
0
Order By: Relevance
“…Our results add to existing research suggesting that merely feeling similarly negative, or generally expressing negative emotions, need not be detrimental to the couple (see Gottman, Coan, Carrere, & Swanson, 1998;Lwi, Haase, Shiota, Newton, & Levenson, 2019;Rohr, Nestler, & Kunzmann, 2019) but instead can indicate togetherness and initiate coordinated action (see Rohr et al, 2019) as long as anger (or another negative emotion, such as contempt) is not directed at the partner, which instead may set off escalating conflict dynamics (see Gottman et al, 1998). Another boundary condition for (shared) negative emotions may be their intensitythe emotions assessed here are those of older couples experiencing what they described as a typical week of their everyday life and thus likely fluctuate rather subtly on rather low levels of intensity.…”
Section: Discussionsupporting
confidence: 81%
“…Our results add to existing research suggesting that merely feeling similarly negative, or generally expressing negative emotions, need not be detrimental to the couple (see Gottman, Coan, Carrere, & Swanson, 1998;Lwi, Haase, Shiota, Newton, & Levenson, 2019;Rohr, Nestler, & Kunzmann, 2019) but instead can indicate togetherness and initiate coordinated action (see Rohr et al, 2019) as long as anger (or another negative emotion, such as contempt) is not directed at the partner, which instead may set off escalating conflict dynamics (see Gottman et al, 1998). Another boundary condition for (shared) negative emotions may be their intensitythe emotions assessed here are those of older couples experiencing what they described as a typical week of their everyday life and thus likely fluctuate rather subtly on rather low levels of intensity.…”
Section: Discussionsupporting
confidence: 81%
“…Third, the lockdown may have led the partners to share and to regulate more their personal emotions within the couple rather than with friends or large family. Thus, couple’s sharing and regulation of emotions could initiate support and contribute to higher togetherness ( Rohr et al, 2019 ). Finally, Williamson (2020) indicated that the experience of the early weeks of the pandemic led partners to become more forgiving and less blaming of their partner’s negative behaviors by attributing them less to their partner’s internal characteristics and more to the stressful pandemic-related context.…”
Section: Discussionmentioning
confidence: 99%
“…First, the lockdown may have led the partners to share and to regulate more their personal emotions within the couple rather than friends or large family. Thus, couple’s sharing and regulation of emotions could initiate support and contribute to higher togetherness (Rohr et al, 2019 ). Second, there is evidence that couples’ shared time is important for both couple quality (e.g.…”
Section: Discussionmentioning
confidence: 99%